The Implementation of Project Based Learning to Improve the Students’ Thinking Skills - Jaya, Aswadi; Hartono, Rudi; Wahyuni, Sri; Yulianto, Henrikus Joko (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2024)
Using the Project-based learning (PjBL) paradigm, this study describes the learning of English subjects using descriptive qualitative research, which include asking fundamental questions, organizing and scheduling, monitoring, product assessment, and evaluation, and applying it to English instruction Low Semester Students. As result, the PjBL can a be used to implement HOTS-based learning. The first stage to the fourth stage is the application of level C4, namely analyzing. The fifth to seventh stages are the application of level C5, namely evaluating. All of these stages are a series in order to reach level C6, namely creating. Thus, it can be concluded that project-based learning is the right learning model to achieve 21st century learning criteria on shaping the students’ demanding skills.